PEMANFAATAN STARBIO TERHADAP KINERJA PRODUKSI PADA AYAM PEDAGING FASE STARTER - Nonok Supartini; Sumarno Sumarno (BUANA SAINS, 2009)
A study that was aimed to elucidate the effect of mixing starbio in feed material on feed consumption, body weight gained, and feed conversion for starter phase of broiler, was conducted at field laboratory of Tribhuwana Tunggadewi University. Eighty broiler male (DOC) of Lohman strain produced by PT Multibreeder Adirama Indonesia were subjected for this study. Feed treatments applied for this study were P0 = Control (no addition of starbio), P1 = 15% starbio addition, P2= 30% starbio addition, and P3 = 45% starbio addition. Results of this study showed that addition of starbio in feed significantly affected feed consumption, body weight gained, and feed conversion of starter phase of broiler